Fermi resonance in Ne, Ar and Kr-matrix infrared spectra of 5-bromouracil - Ivanov, A.Yu.; Rubin, Yu.V.; Egupov, S.A.; Belous, L.F.; Karachevtsev, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Low-temperature matrix isolation Fourier-transform infrared spectroscopy and quantum-chemical calculations with DFT/B3LYP and MP2 methods were used for investigation of isolated 5-bromouracil (BrU) molecules. Only one tautomeric form of BrU was dominated in the low-temperature Ne, Ar, and Kr matrices. It was revealed that population of minor hydroxy-tautomers did not exceed 0.2%. Appearance of additional absorption bands in the region of stretching vibrations nCO (about 1710 cm–1) as well as of deformation ones (1297, 1093, 901 cm–1) was explained by Fermi resonance. In Ne matrices the peak intensities of absorption bands assigned to the out-of-plane vibrations of the ring and exocyclic atoms were decreased sharply. For the first time, least square method with the using of polynomial was proposed for the corrective scaling of calculated frequencies of vibrations. It is shown that the correction of calculated frequencies with the polynomial of degree two permits to decrease the root-mean-square discrepancy between the calculated and experimental ones to 4–5 cm–1 in the region of 1500–500 cm–1. The same polynomial may be applied for the correction of spectra of molecules with a similar structure.